The Association Between Feeding Practices and History of Diarrhea with Nutritional Status of Toddlers - Lulu Indria Setyani; Khoirul Anwar (Faculty of Public Health Universitas Indonesia, 2022)
The age of 0-59 months is a phase of basic life formation that is vulnerable to nutritional problems. Causes such as infectious diseases and parenting. The purpose of this research is to analyze the relationship between feeding practices and history of diarrhea with the nutritional status of children under five. This study used a cross-sectional design. Samples were taken by purposive sampling of as many as 96 toddlers. Data were collected by direct measurement of weight scales, stature meters, and interviews using the main questionnaire and the modified CFQ questionnaire. The statistical tests used were the chi-square test and fisher's exact test. A total of 28.1% of respondents practice inappropriate feeding and 47.9% of children under five have a history of diarrhea. There is a relationship between feeding practices and underweight (p=0.000), stunting (p=0.000), and wasting (p=0.000). There was a relationship between a history of diarrhea and being underweight (p=0.043), but there was no relationship between stunting (p=0.073) and wasting (p=0.063).Keywords: diarrhea, feeding, nutritional status, toddlers